The house on Graveyard Lane - Edwards, Martin, 1955- (Edwards, Martin, 1955-. Rachel Savernake Golden Age mystery., 2024)
""I want you to solve my murder," said the woman in white. Rachel Savernake gave a sardonic smile. "Quite a challenge." The woman in white-surreal artist Damaris Gethin-has invited a select group to the opening of her exhibit "Artist in Crime," held in the eerie subterranean Hades Gallery. As costumed models reenact famously violent deaths, the artist herself portrays Marie Antoinette on the day of her execution, complete with a guillotine on the stage. It's not a prop; within ten minutes of Rachel's promise to solve Damaris's future murder, the artist slips her neck into the collar of the device and the very real blade sends her head rolling at the feet of her horrified audience. As everyone reels from the shock, Rachel quickly learns that Damaris herself accomplished the deed with the push of a button-a suicide. So then why did she ask Rachel to solve her "murder?" Keen for the hunt, Rachel begins sniffing around the other invited guests, including a former lover with shady financial dealings, his widowed sister-in-law, and her has-been songwriter friend. Meanwhile, crime reporter Jacob Flint-also in attendance, in hopes of meeting celebrated French beauty Kiki de Villiers, allows his fascination with her to endanger his own life when a ruthless gangster returns to London, looking to take back what's his. Equal parts thriller and whodunit, THE HOUSE ON GRAVEYARD LANE leads Rachel and Jacob into a viper's pit of suspects, each sneakier and more venomous than the last"--